2006
DOI: 10.1111/j.1365-3148.2006.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the economic value of the INTERCEPT blood system in Belgium

Abstract: Emerging pathogens continue to threaten blood safety, requiring novel safety approaches. INTERCEPT Blood System for platelets (IBSP) inactivates pathogens, aiming at eliminating the risk of transmitting current and emerging pathogens. The objective was to evaluate the incremental cost-effectiveness ratio (ICER) for IBSP in Belgium. A decision model comparing a 'world with IBSP' to a 'world without IBSP' calculates lifetime costs and 'quality adjusted life years' (QALYs) following platelet transfusion in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…A cost increase of € 50 per PC lies in between the estimated additional costs from cost effectiveness analyses for PI in various countries [29,30,31]. These models refer to known risks of bacterial and viral infections and the respective disease consequences or to potential infectious risks of re-/emerging pathogens transmissible by PCs, which would all be avoided by PI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cost increase of € 50 per PC lies in between the estimated additional costs from cost effectiveness analyses for PI in various countries [29,30,31]. These models refer to known risks of bacterial and viral infections and the respective disease consequences or to potential infectious risks of re-/emerging pathogens transmissible by PCs, which would all be avoided by PI.…”
Section: Discussionmentioning
confidence: 99%
“…These models refer to known risks of bacterial and viral infections and the respective disease consequences or to potential infectious risks of re-/emerging pathogens transmissible by PCs, which would all be avoided by PI. In the context of costs for other accepted blood safety interventions in the developed world, PI for PCs appears to be cost-effective to most authors [29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Belgian study, implementation of an amotosalen-based pathogen reduction system for platelets was found to be cost-effective compared with the initial national system (measured in terms of lifetime costs and quality adjusted life years (QALYs)). A range of incremental cost-effectiveness ratios were observed (in absence of emerging pathogens) from 3,459,201 €/QALY to 195,364 €/QALY), and the mean threshold of emerging infection risk for the pathogen reduction system ranged from 1/1079 to 1/2858 transfusion [124]. In addition, a model that was developed from a Dutch study found that implementation of pathogen inactivation as a routine procedure would be a cost-effective measure (measuring cost-effectiveness in net costs per life year gained (LYG)); net costs per LYG with pathogen inactivation were estimated at €554,000 in the baseline-weighted average over three patient groups (90% simulation interval €354,000–1092,500).…”
Section: Cost Considerationsmentioning
confidence: 99%
“…The Panel appreciates that precaution must be tempered by the logic of cost‐benefit analysis with its focus on scarcity and estimates of risk 65 . Country‐specific studies of different PI technologies have been published, and the strengths and limitations of the existing studies were analyzed at this conference 66‐72 . Economic evaluations of all PI procedures should be conducted.…”
Section: How Should the Costs And/or Benefits Of Pi Be Assessed?mentioning
confidence: 99%